Experimental Verification of Wind Power Generation System Using Diode Bridge Rectifier Circuit with Wind Turbine Simulator - Sirichai Tammaruckwattana; Sitthaphat Reangkittakarn; Natchanon Suppaadirek; Kazuhiro Ohyama (International Review of Electrical Engineering (IREE), 2022)
This paper presents Wind Power Generation System using Diode Bridge Rectifier (WPGS-DBR method). Experimental results have been obtained by Wind Turbine Simulator (WTS). The WTS emulates wind turbine behavior using a servo motor as a drive system. Mechanical torque references used to drive the motor are calculated using wind turbine data such as wing blade, wind velocity, and wind turbine rotation speed. DBR method has three-mode control for three ranges of wind speed: low, medium, and high, respectively. In low and medium mode, the control system adjusts the armature current of a generator and DC link voltage with a Vector-Controlled Inverter (VCI) to control wind turbine speed. In high mode, the control system modulates the pitch angle of the wind turbine using a pitch angle control system for controlling wind turbine rotational speed. The DBR simplifies the maintenance of WPGS while improving reliability. In addition, the DBR method costs less compared with the WPGS using a PWM converter.
Keywords: Wind Turbine Control Systems; Electric Motor Design and Analysis; Real-time simulation and control systems